Association between Enhancing Learning Needs and Demographic Characteristic of Patients with Myocardial Infarction: العلاقة بين تعزيز احتياجات التعلم والخصائص الديموغرافية لمرضى احتشاء عضلة القلب - Zainab Kazem, (Iraqi National Journal of Nursing Specialties, 2022)
Abstract Objectives: To find out the association between enhancing learning needs and demographic characteristic of (gender, education level and age). Methods: This study was conducted on purposive sample was selected to obtain representative and accurate data consisting of (90) patients who are in a peroid of recovering from myocardial infarction at Missan Center for Cardiac Diseases and Surgery, (10) patients were excluded for the pilot study, Data were analyzed using descriptive statistical data analysis approach of frequency, percentage,  and analysis of variance (ANOVA).Results: The study finding shows, there was significant relationship between gender and patients’ learning needs in pretest and posttest at (P value > .000), while no significant relationship was found with patients’ age and level of education with their learning needs.Recommendations: The study recommend that the future research on perceived learning needs could focus at the needs of patients from other groups, such as individuals with cardiac arrhythmia but no MI. Further research into the perceived learning needs of these patient populations could be conducted.